PERKEMBANGAN FINTECH TERHADAP INOVASI EKONOMI DIGITAL DALAM PERSPEKTIF HUKUM BISNIS ISLAM - Muhammad Fadli Ikhwan; Ganesta Putrya Awara; Sandria Zhafrani (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study explores the rapid development of financial technology (fintech) and its role in driving digital economic innovation from the perspective of Islamic business law. Using a descriptive qualitative method through literature review, the research analyzes fintech's impact on financial accessibility, economic participation, and legal compliance with Islamic principles. Fintech services, such as peer-to-peer lending, digital wallets, and investment platforms, offer numerous benefits including efficiency, financial inclusion, and economic democratization. However, challenges arise when fintech practices potentially involve elements prohibited in Islamic law, such as riba (interest), gharar (uncertainty), and maisir (speculation). This study emphasizes the importance of aligning fintech implementation with sharia principles, as regulated by national institutions like DSN-MUI, OJK, and Bank Indonesia. The findings highlight the need for fintech developers, regulators, and users to uphold transparency, fairness, and religious compliance to ensure the ethical advancement of digital finance. The study also calls for greater public literacy and regulatory support for sharia-compliant fintech innovation.Keywords: digital economy, fintech, innovation, Islamic business law, sharia compliance